The effect of a one-time mindfulness intervention on body and mind in healthy adolescents using multimodal measurements - Ecker, Angelika; Fritsch, Charlotte; Schleicher, Daniel; Jacob, Ricarda; Kandsperger, Stephanie; Brunner, Romuald; Jarvers, Irina (Frontiers in Psychiatry, 2025)
BackgroundMindfulness-based interventions can improve psychological well-being and reduce symptoms of mental burden, including among adolescents. Relationships between basic mindfulness (trait mindfulness) and the immediate effects of a single mindfulness intervention have not been thoroughly researched, especially in adolescents. In this study, we aimed to elucidate these aspects by using a multimodal approach—measuring the effect of a single mindfulness intervention on both subjective and physiological parameters.MethodsA total of 78 healthy adolescents (12–19 years of age, 50% female) were assigned to either a mindfulness or an active control group. Before and after the interventions, subjective parameters (mood, stress, and state mindfulness) were assessed using bipolar visual analogue scales. Physiological parameters (heart rate and heart rate variability) were measured before and during the interventions. Participants also completed the Self-Compassion Scale (SCS-D) with the subscale “mindfulness” as an assessment of trait mindfulness, and the State-Trait Anxiety-Depression Inventory (STADI).ResultsOur results showed no significant interactions between time and intervention, either subjectively or physiologically. For heart rate, we found a main effect of time. For all subjective parameters, we observed a main effect of trait mindfulness. Age was a relevant factor for heart rate and state mindfulness, suggesting age effects. We also observed strong correlations between trait mindfulness, trait anxiety, and depression scores.ConclusionA single mindfulness intervention had no immediate observable effects in our healthy adolescent sample, and possible reasons for this finding are discussed. Nevertheless, the present data show the potential for increased resilience through mindfulness in adolescence.